Inequality and poverty re-examined - Jenkins, Stephen P.; Micklewright, John (Oxford University Press, 2007)
The issues surrounding poverty and inequality continue to be of central concern to academics, politicians and policymakers but the way in which we seek to analyse them continues to change. This is a guide to some of the new approaches that have been developed, while also making a contribution to the ongoing public debate.